2016
DOI: 10.1002/pon.4207
|View full text |Cite
|
Sign up to set email alerts
|

Cancer disclosure-account from a pediatric oncology ward in Egypt

Abstract: Our findings indicate that cancer disclosure at the Children's Cancer Hospital is to a certain degree common; yet even when disclosure does take place, it is mainly in the absence of the child. Moreover, the information provided during the conversation may not be fully comprehended by the parent or the child because of the physician's misleading use of terms when disclosing the disease. Therefore, better practice should be developed for disease disclosure, and proper communication should be established between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…A majority of the studies (60%) addressed challenges around direct or indirect diagnostic disclosure to children, including differences in provider‐caregiver and provider‐patient communication 21,24,25,35,53 and disclosure practice variation based on child age 31,38 . Most studies focused on caregiver perceptions regarding the involvement of their child in communication 35,36,47,53 .…”
Section: Resultsmentioning
confidence: 99%
“…A majority of the studies (60%) addressed challenges around direct or indirect diagnostic disclosure to children, including differences in provider‐caregiver and provider‐patient communication 21,24,25,35,53 and disclosure practice variation based on child age 31,38 . Most studies focused on caregiver perceptions regarding the involvement of their child in communication 35,36,47,53 .…”
Section: Resultsmentioning
confidence: 99%
“…This explains, to some extent, why the caregivers exhibit a horrendous feeling when they receive the diagnosis which could be comparable to receiving a death sentence of one’s child. This phenomenon is addressed in a study by El Malla et al which found the caregivers refrained from, and deliberately avoided, using the word cancer [ 5 ]. It is also addressed in several other studies on adult cancer patients in this region such as the study in Saudi Arabia where family members desired more information but clearly discouraged disclosure and information provision to the adult patients [ 14 , 15 , 16 , 17 , 18 ] or Pakistan where similar patterns were found among adult cancer patients and their family members [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on this study, a large-scale prospective study was conducted in 2008 and was followed up in 2013 [ 3 , 4 , 5 , 6 ] including two comprehensive, structured interview questionnaires with 304 caregivers to newly diagnosed children with cancer starting their first chemotherapy treatment, followed again by the third chemotherapy treatment, and finally surveyed five years later as a mean of a five-years survival rate follow-up [ 6 ]. The study was conducted at the Children’s Cancer Hospital in Egypt (CCHE), the largest pediatric oncology hospital in the region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This explains why breaking the news to the child's family is an important step. 24 It is not surprising, then, that after their child's diagnosis, parents often reprogram their lives to adjust to the new situation and often begin to look for solutions-both inside or outside hospitals. Nurses may not be happy with pursuit of alternative therapies, 25 so they feel a moral duty, which goes beyond the scope of their job, to warn against practices that may pose a danger or harm.…”
Section: Nature Of Cancermentioning
confidence: 99%